2023
DOI: 10.3390/ma16103879
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Exceptionally Durable Photooxidation Properties on Co3O4/g-C3N4 Surfaces

Abstract: Water pollution is a significant social issue that endangers human health. The technology for the photocatalytic degradation of organic pollutants in water can directly utilize solar energy and has a promising future. A novel Co3O4/g-C3N4 type-II heterojunction material was prepared by hydrothermal and calcination strategies and used for the economical photocatalytic degradation of rhodamine B (RhB) in water. Benefitting the development of type-II heterojunction structure, the separation and transfer of photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The photocatalytic degradation of organic pollutants in water is an effective method to deal with water pollution. Dai et al [9] prepared a novel Co 3 O 4 /g-C 3 N 4 composite photocatalyst and used it for the photocatalytic degradation of rhodamine B in water. They found that the type II heterojunction was formed between the Co 3 O 4 and g-C 3 N 4 , and that the type II heterojunction significantly enhanced the transfer and separation of photogenerated electrons and holes in the Co 3 O 4 /g-C 3 N 4 photocatalyst.…”
mentioning
confidence: 99%
“…The photocatalytic degradation of organic pollutants in water is an effective method to deal with water pollution. Dai et al [9] prepared a novel Co 3 O 4 /g-C 3 N 4 composite photocatalyst and used it for the photocatalytic degradation of rhodamine B in water. They found that the type II heterojunction was formed between the Co 3 O 4 and g-C 3 N 4 , and that the type II heterojunction significantly enhanced the transfer and separation of photogenerated electrons and holes in the Co 3 O 4 /g-C 3 N 4 photocatalyst.…”
mentioning
confidence: 99%